MULTIDIMENSIONAL RELIABILITY OF INSTRUMENT STUDENTS’ SATISFACTION USING CONFIRMATORY FACTOR ANALYSIS - Gaguk Margono (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
The purpose of this paper is to compare unidimensional reliability and multidimensionalreliability of instrument students’ satisfaction as an internal costumer. Multidimensionalreliability measurement is rarely used in the field of research. Multidimensional reliability isestimated by using Confirmatory Factor Analysis (CFA) on the Structural Equation Model(SEM). Measurements and calculations are described in this article using instrument students’satisfaction as an internal costumer. Survey method used in this study and sampling used simplerandom sampling. This instrument has been tried out to 173 students. The result is concludedthat the measuringinstrument of students’ satisfaction as an internal costumer by usingmultidimensional reliability coefficient has higher accuracy when compared with aunidimensional reliability coefficient. Expected in advanced research used another formulamultidimensional reliability, including when using SEM.Keywords: multidimensional reliability, instrumentof students’ satisfaction as an internalcostumer, confirmatory factor analysis.